Horseradish peroxidase-mediated decolourization of Orange II: modelling hydrogen peroxide utilization efficiency at different pH values - Morales Urrea, Diego Alberto (2018)
Enzymatic decolourization of azo-dyes could be a cost-competitive alternative compared to physicochemical or microbiological methods. Stoichiometric and kinetic features of peroxidase-mediated decolourization of azo-dyes by hydrogen peroxide (P) are central for designing purposes. In this work, a modified version of the Dunford mechanism of peroxidases was developed. The proposed model takes into account the inhibition of peroxidases by high concentrations of P, the substrate-dependant catalatic activity of peroxidases (e.g. the decomposition of P to water and oxygen), the generation of oxidation products (OP) and the effect of pH on the decolourization kinetics of the azo-dye Orange II (OII). To obtain the parameters of the proposed model, two series of experiments were performed. In the first set, the effects of initial P concentration (0.01–0.12 mM) and pH (5–10) on the decolourization degree were studied at a constant initial OII concentration (0.045 mM). Obtained results showed that at pH 9–10 and low initial P concentrations, the consumption of P was mainly to oxidize OII. From the proposed model, an expression for the decolourization degree was obtained. In the second set of experiments, the effect of the initial concentrations of OII (0.023–0.090 mM), P (0.02–4.7 mM), HRP (34–136 mg/L) and pH (5–10) on the initial specific decolourization rate (q 0 ) was studied. As a general rule, a noticeable increase in q 0 was observed for pHs higher than 7. For a given pH, q 0 increased as a function of the initial OII concentration. Besides, there was an inhibitory effect of high P concentrations on q 0 . To asses the possibility of reusing the enzyme, repeated additions of OII and P were performed. Results showed that the enzyme remained active after six reuse cycles. A satisfactory accordance between the change of the absorbance during these experiments and absorbances calculated using the proposed model was obtained. Considering that this set of data was not used during the fitting procedure of the model, the agreement between predicted and experimental absorbances provides a powerful validation of the model developed in the present work.